MATHEMATICAL PROBLEM-SOLVING SKILLS AND STUDENTS' LEARNING INDEPENDENCE THROUGH PMRI BASED ON ENGINEERING DESIGN THINKING: Bengkulu, Indonesia - Leni Pitriyani; Risnanosanti; Ristontowi; Rahmat Jumri; Adi Asmara (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to observe the differences in students' mathematical problem-solving abilities and learning independence in learning with the Indonesian Realistic Mathematics Education (PMRI) approach based on Engineering Design Thinking (EDT), the Indonesian Realistic Mathematics Education (PMRI) approach, and conventional learning. This study is a quasi-experimental study with a pretest–posttest control group design. The study population was all seventh-grade students of SMP Negeri 7 Bengkulu City in the 2025/2026 academic year. Data analysis was carried out using one-way ANOVA. The results showed that there were significant differences in students' mathematical problem-solving abilities taught with the PMRI approach based on EDT, PMRI, and conventional learning (F = 3.629; p = 0.031 < 0.05). The average posttest of students' mathematical problem-solving abilities in the PMRI class based on Engineering Design Thinking was 28.75, the PMRI class was 26.84, and the conventional learning class was 24.42. In addition, there was a significant difference in student learning independence between the three learning groups (F = 3.734; p = 0.029 < 0.05). The average student learning independence in the EDT-based PMRI class was 73.94, higher than the PMRI class (68.95) and the conventional learning class (68.13). Based on these results, EDT-based PMRI learning is more effective in improving students' mathematical problem-solving abilities and learning independence. Keywords: PMRI, Engineering Design Thinking (EDT), Mathematical Problem Solving Ability, Learning Independence.